2006
DOI: 10.3354/meps318165
|View full text |Cite
|
Sign up to set email alerts
|

Allelochemical defense against epibiosis in the macroalga Caulerpa racemosa var. turbinata

Abstract: The abundance and diversity of microorganisms on the surface of the tropical green macroalga Caulerpa racemosa var. turbinata and the effect of algal surface and waterborne compounds on fouling organisms were investigated both in laboratory and field experiments. As shown via electron microscopic enumeration, the abundance of epibiotic bacteria and diatoms on algal frond surfaces was not significantly different from the reference biofilms harvested from stones in the C. racemosa habitat. The analysis of Termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…The band patterns obtained were analyzed using the GelBuddy software (www.gelbuddy.org) and compared using the Primer software package. To this end, migration distance was assimilated to species and the sum of presences/absences of bands at given distances constituted the community composition, which was compared among samples by a Bray-Curtis similarity analysis (for more details on the RFLP and its analysis, see Dobretsov et al 2006a). In order to identify the bacterial species that were represented by different bands, the pre-cut DNA was cloned using the pCR4-Topo TA cloning kit (Invitrogen) according to the user's manual.…”
Section: Methodsmentioning
confidence: 99%
“…The band patterns obtained were analyzed using the GelBuddy software (www.gelbuddy.org) and compared using the Primer software package. To this end, migration distance was assimilated to species and the sum of presences/absences of bands at given distances constituted the community composition, which was compared among samples by a Bray-Curtis similarity analysis (for more details on the RFLP and its analysis, see Dobretsov et al 2006a). In order to identify the bacterial species that were represented by different bands, the pre-cut DNA was cloned using the pCR4-Topo TA cloning kit (Invitrogen) according to the user's manual.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, capability to inhibit or modify the very first fouling stages by bacteria may be especially important, as it may prevent or reduce successive epibiotism. Macroalgae commonly contain antimicrobial metabolites (e.g., Hellio et al 2001) and the microbial community on algal frond surfaces has been found to differ from that of inanimate, undefended substrates (Dobretsov et al 2006a), indicating that macroalgae may be able to affect the formation of bacterial biofilm and thereby influencing successive fouling by macroorganisms. Oxidative bursts, i.e., rapid production of active oxygen species such as hydrogen peroxide and hydroxyl radicals from cells when they come into contact with pathogens, may be involved in encounters with epiphytic bacteria, fungi, or other organisms (reviewed in Steinberg and de Nys 2002;Potin et al 2002; see also Chap.…”
Section: Epibiotism As a Natural Enemymentioning
confidence: 99%
“…Allelopathic activities have also been reported for extracts of Caulerpa spp. and caulerpenyne toward microalgae (Lemee et al, 1997;Smyrniotopoulos et al, 2003) and the fouling polychaete worm Hydroides elegans (Dobretsov et al, 2006).…”
Section: Caulerpenynementioning
confidence: 99%